Self-Organized Patterns in Gas-Discharge: Particle-Like Behaviour and Dissipative Solitons - Purwins, H-G (AIP conference proceedings, 2008)
The understanding of self-organise patterns in spatially extended nonlinear dissipative systems (SOPs) is one of the most challenging subjects in modern natural sciences. In the last 20 years it turned out that research in the field of low temperature gas-discharge can help to obtain insight into important aspect of SOPs. At the same time, due to the practical relevance of plasma systems one might expect interesting applications. In the present paper the focus is on self-organised filamentary patterns in planar dc and ac systems with high ohmic and dielectric barrier, respectively. - In the discharge plane of these systems filaments show up as spots which are also referred to as dissipative solitons (DSs). In many respect experimentally detected DSs exhibit particle-like behaviour. Among other things, isolated stationary or travelling DSs, stationary, travelling or rotating 'molecules' and various kinds of many-body systems have been observed. Also scattering, generation and annihilation of DSs are frequent phenomena. - At least some of these patterns can be described quantitatively in terms of a drift diffusion model. It is also demonstrated that a simple reaction diffusion model allows for an intuitive understanding of many of the observed phenomena. At the same time this model is the basis for a theoretical foundation of the particle picture and the experimentally observed universal behaviour of SOPs. - Finally some hypothetical applications are discussed.